Use of nilotinib in the diabetic patient - Carmen Tomaselli (Clinical Management Issues, 2015)
A 42-year-old man, diabetic patient, after CML Ph+ diagnosis started a treatment with imatinib reaching both CHR and CCyR within 6 months. Because of two episodes of vitreous haemorrhage the treatment was discontinued for four months with the lost of the CCyR and the maintenance of the CHR. The patient begun second line therapy with nilotinib, another TK inhibitor, recovering CCyR after 3 months and MMolR after 12 months, and keeping them up after 18 months of treatment. Nilotinib related side effects were transient rash and first degree arthromyalgia that occurred during the first month of therapy. In this case nilotinib therapy has shown to be safe and effective also for diabetic patients with intolerance to imatinib.